Upbringing Towards the “Highest” Values in the Activities and Program of “Eleusis” During the Period of National Captivity - Głowacka-Sobiech, Edyta (Biuletyn Historii Wychowania, 2018)
The turn of the 19th and 20th centuries brought an unprecedented number of youth organizations and movements in Galicia, which can be divided into three basic groups: the sports-tourism-gymnastic movement, the military movement and the ethical-revival movement. One of them was “Eleusis” movement initiated by Wincenty Lutosławski (1863–1954), a well-known philosopher, member of the Academy of Skills, and also the brother of Kazimierz Lutosławski, the legendary creator of the Scout Cross. “Eleusis” existed in the years 1903–1920, its aim was to prepare young Poles for the struggle for independence by educating their morals. “Eleusis” rejected violence and armed struggle. “Eleusis” was a strictly Catholic organization – a kind of secular order. However, it never received the official blessing of the Catholic Church. Many Eleusis members later joined the ranks of the Polish scouts and it is thanks to the Eleusian spirit that Polish scouting has the rule of alcohol and tobacco abstinence in its Scouting Law. Whereas, the meaning and influence of scouts on Polish youth is undisputed today.